Cardiac CT Imaging Diagnosis of Cardiovascular Disease - Budoff, Matthew J.; Shinbane, Jerold S. (Springer International Publishing : Imprint: Springer, 2016)
This book collates the current knowledge in cardiovascular CT and presents this in a clinically relevant and practical format appropriate for all who use the modality. The field has experienced continued rapid evolution due to advances in technology, the expanded spectrum of cardiovascular applications and significant growth in published data. As increasing numbers have access to CT scanners, Cardiac CT Imaging: Diagnosis of Cardiovascular Disease, Third Edition provides all the relevant information on the use of this modality. This extensive revision of this well-respected textbook brings the reader up-to-date with the technique, with chapters supplied by an experienced set of contributing authors and representing the full spectrum of cardiac CT. It thus represents an essential purchase for those preparing for board examinations, all training to use this modality, and those already using cardiovascular CT on a day-to-day basis who want to stay current.